PROFESSIONAL CONSULTING, PLANNING AND DESIGN OF REGIONAL DEVELOPMENT IN THE FACE OF INCREASING UNCERTAINTIES AND RISKS - G. A. Fomenko; M. A. Fomenko (Стратегические решения и риск-менеджмент)
The article reveals features of the ongoing transformations in the field of consulting, planning and design in the field of regional development in the face of increasing uncertainties and risks, primarily related to climate change and biodiversity loss. It shows that the very basis of such work is significantly changing, as the world-system becomes more complex, during the transition from the concept of an “empty” world to a “full” world. This change includes increasing emphasis on ensuring the resilience of human-dominated ecosystems, a change in decision-making, using behavioral a “responsible” human model that best meets the needs of inclusive sustainable development.The authors define features of consulting, planning and design of regional development in the face of increasing uncertainties and risks, as a special type of thinking activity, in a situation of approaching radical uncertainty. The article shows the necessity of supplementing natural science approaches with the tools and practices of post-normal science and the narrative theory of beliefs, as well as the ideas of K. Friston, implemented within his dynamic causal model.Such an approach is based on a systematic approach to decision-making in regional development and pays special attention to the adaptation of individuals and communities to high risks and uncertainties, primarily climatic and natural. It helps to better reflect the diversity of geographical conditions, to clarify the range of effective solutions for sustainable development of regions and increase the long-term resilience of business.